ORE-BEARING METASOMATITES OF PERGA AREA AND KOROSTEN PLUTON GRANITOIDS (UKRAINIAN SHIELD): GENETIC RELATIONS ON THE BASIS OF GEOCHEMICAL MODELLING - Lazareva, І.; Shnyukov, S.; Aleksieienko, A.; Gavryliv, L. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
Geochemistry of the most typical ore-bearing (sulfide-rare metal mineralization) metasomatites formation within tectonic zones (Perga area) spatially associated with Precambrian (1.75-1.8 Ga) Korosten anorthosite-rapakivigranite pluton (Ukrainian Shield) was investigated in detail. Major and trace elements behavior during the multistage alteration of predominantly granites was studied. All investigated altered varieties were classified into several geochemical types of alteration which result in formation of corresponding metasomatites during the multistage processes: (1) Fe – Mg – Na – K – Zn, Pb, Nb, Rb, Cs, Cd (Be, Li, Ta etc.) – apogranites, albitites-I, albite-microcline, microclinealbite, siderophyllite-feldspar and siderophyllite metasomatites; (1a) Na – Nb, Sn (Ta, Be etc.) – albitites-II; (2) Si – (Sn, Be, W etc.) – apogranites and quartz-muscovite greisens. Metasomatites of the 1st (main) type are widely distributed and contain the most of related economic mineralization. Geochemical data obtained were compared to hypothetical compositions of metasomatites, calculated from predesigned geochemical model of the Korosten pluton granitoid evolution based on fractional crystallization equations. A set of zircon, apatite and monazite solubility equations in silicate melts was used in the model designed to estimate magma crystallization temperature in deep chamber and the level of its saturation in H2O. Dependences CL=C0fD-1 (C0 = element concentration in parent magma, CL = element concentration in residual melt, f = weight fraction of liquid phase in magma chamber, D = bulk distribution coefficient of the element) for Zn, Pb, Nb, F and Cl show inverse nature. Their extremum points indicate f value when residual melt reaches saturation in water (aqueous fluid separation beginning). This makes it possible to calculate the KF/L = CF/CL (CF – element concentration in fluid) values and to estimate the Zn, Pb, Nb concentrations in hypothetical (model) metasomatites. Model (calculated) element concentrations correspond to the composition of natural ore-bearing metasomatites of the Perga area. These results confirm the hypothesis that high-temperature metalbearing fluids, which formed metasomatites, were produced by the Korosten pluton granitoids during their magmatic evolution.
Keywords: metasomatites; granite; trace element; magmatic evolution; fluid separation; fluid/melt distribution coefficient; rock alteration; ore mineralization